Gambaran Perilaku Perawat Dalam Penerapan Kesehatan Dan Keselamatan Kerja - Zulfikar Lating; Ira Deseilla Pawa; Ira Sandi Tunny (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2024)
Occupational Health and Safety is a concept of systematic and comprehensive K3 management in a complete management system through the process of planning, implementing, measuring, and supervising. The purpose of K3 related to machinery, equipment, workplace foundations and workplace environment is to prevent accidents and illnesses due to work, provide protection to production sources so that they can increase efficiency and productivity. The purpose of the study is to identify the description of nurse behavior in the implementation of occupational health and safety. The research design used was a descriptive survey, with a total sample of 55 respondents. The sampling technique used was simple random sampling of 55 people. The results of this study were for the highest knowledge with the adequate category of 31 respondents with a percentage (56.4), and for the highest attitude with the sufficient category of 28 respondents with a percentage (50.9), and for the highest action with a sufficient category of 32 respondents with a percentage (58.2), and for the implementation of the highest K3 with a sufficient category of 37 respondents with a percentage (67.3).